2016
DOI: 10.1021/acsami.5b10336
|View full text |Cite
|
Sign up to set email alerts
|

Photodetection in Hybrid Single-Layer Graphene/Fully Coherent Germanium Island Nanostructures Selectively Grown on Silicon Nanotip Patterns

Abstract: Dislocation networks are one of the most principle sources deteriorating the performances of devices based on lattice-mismatched heteroepitaxial systems. We demonstrate here a technique enabling fully coherent Ge islands selectively grown on nano-tip patterned Si (001) substrates. The Si-tip patterned substrate, fabricated by complementary metal-oxidesemiconductor (CMOS) compatible nanotechnology, features ~50 nm wide Si areas emerging from a SiO 2 matrix and arranged in an ordered lattice. Molecular beam epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…Therefore, the dark current under a low reverse bias (from 0 V to −2 V) is much lower than under a low forward bias (form 0 V to +2 V), as shown in Figure 4 b,c. It is noteworthy that the SBH tunable behavior of the camphor-based CVD graphene/p-Si heterostructure is consistent with the numerous study results of the conventional CVD bilayer graphene/Si heterostructures reported previously [ 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Measurement Results and Discussionsupporting
confidence: 90%
“…Therefore, the dark current under a low reverse bias (from 0 V to −2 V) is much lower than under a low forward bias (form 0 V to +2 V), as shown in Figure 4 b,c. It is noteworthy that the SBH tunable behavior of the camphor-based CVD graphene/p-Si heterostructure is consistent with the numerous study results of the conventional CVD bilayer graphene/Si heterostructures reported previously [ 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Measurement Results and Discussionsupporting
confidence: 90%
“…However, notice that it can be straightforwardly used to investigate realistic shapes as shown in Refs. [37][38][39].…”
Section: Elastic Vs Plastic Relaxation: Theorymentioning
confidence: 99%
“…However, notice that it can be straightforwardly used to investigate realistic shapes as shown in Refs. [37][38][39]. Following the work in [35], the typical elastic field of VHEs as in Figure 7a can be computed by FEM calculations and it is illustrated in Figure 7b for a pure Ge epilayer by means of the hydrostatic stress .…”
Section: Elastic Vs Plastic Relaxation: Theorymentioning
confidence: 99%
“…Zeng et al reported a monolayer graphene/Ge Schottky junction based IR photodetector with a higher operation speed . Niu et al also reported a high‐performance IR photodetector based on a monolayer graphene/Ge island/Si nanotip structure by growing the dislocation‐free Ge islands on a Si nanotip substrate . In these cases, the best responsivity was ≈62 mA W −1 , which is still substantially lower than the commercially available Ge IR detectors (responsivity ≈0.8 A W −1 with 1–100 µA cm −2 of dark current).…”
mentioning
confidence: 99%